METHODOLOGY FOR OBTAINING CROSS-SECTIONAL ROAD SURFACE PROFILES USING LASER SCANNING DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Road infrastructure is critical to the economy, providing mobility for people and cargo, and contributing to economic growth. Modern technologies, particularly 3D laser scanning, play a significant role in the monitoring, evaluation, and operation of infrastructure. As part of this study, the AU20 laser scanning system was used to obtain transverse road surface profiles on a certain section of the Yerevan Tbilisi Highway. The scan data was processed in the ArmRef02 coordinate system. The main objectives of the survey are:•    develop a methodology to automatically separate the road surface from the 3D point cloud.•    Identify the pivotal and central axes of the path through spatial analysis.•    Compare the resulting profiles with the technical norms and suggest possible improvements.The results showed that existing technical abnormalities have a negative impact on drainage efficiency and traffic safety. Adherence to local and international regulatory standards can contribute to improved road operation and sustainable development of transport networks.
Keywords: GNSS; LiDAR; MLS; field authentication; Tibetan Highway